Artificial Intelligence Based Al-Qur'an Learning Media Design “Tarteel” on Fastabiqul Khoirot Material - Eka Rohmatun Nazilah; Nadia Fatchu Ilmi (International Forum of Researchers and Lecturers, 2025)
This study discusses the design of artificial intelligence-based Al-Qur'an learning media through the Tahseen platform with a focus on the theme of Fastabiqul Khoirot. Al-Qur'an learning in the digital era faces challenges in the form of a lack of interest and involvement of students due to monotonous conventional methods. This study, through library research, aims to provide an overview of how to increase the efficiency of Al-Qur'an learning by integrating AI